Human rights and conflict resolution bridging the theoretical and practical divide - Fuentes Julio, Claudia; Drumond, Paula (Global institutions series, 2018)
Human rights and conflict resolution have been traditionally perceived as two separate fields, sometimes in competition or in tension and occasionally with contradictory approaches towards achieving a lasting peace. The chapters in this volume navigate the relationship between human rights and conflict resolution by fleshing out practical, conceptual, and institutional encounters of the two agendas and engaging with lessons learned and windows of opportunities for mutual learning.